Joint Liability Based Financing To Prevent Non-Performing Financing In Bank Wakaf Mikro - Purwanto; Abdul Ghofur; Shodiq Abdullah (Faculty of Islamic Economics and Business of UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
The Indonesian government has made various efforts to reduce it, one of which is establishing a Micro Waqf Bank. The focus of the establishment of the Bank Wakaf Mikro is to empower the poor by providing assistance and providing microfinance for productive activities. Interesting to assess is the financing mechanism applied, namely joint liability. The purpose of this study is to examine whether joint liability-based financing can prevent non-performing financing. Data were collected from 215 respondents from Micro Waqf Bank customers in Magelang Regency. Data analysis was carried out statistically by using Structural Equation Model (SEM) Partial Least Square. The results show that joint liability-based financing has a significant effect on preventing non-performing financing. This means that joint liability based on Bank Wakaf Mikro can prevent defaults or non-performing financing. This means that joint liability based on the distribution of fund financing by Bank Wakaf Mikro can prevent defaults or non-performing financing. Problem financing in joint liability-based financing can be prevented because of the necessity of forming a group when applying for financing, so prospective customers will choose group members who have integrity and can be trusted.